The Impacts of Learning Supervision and Work Motivation on the Work Commitment of Public Junior High School Teachers - Revita, Yuni; Rifma; Rusdinal; Anisah (Universitas Jambi, Indonesia, 2024)
This research aims to reveal the influence of learning supervision and work motivation on the work commitment of public junior high schools in Padang City. The hypotheses proposed in this research are (1) the significant influence of learning supervision on work commitment, (2) the significant influence of work motivation on work commitment, and (3) the significant influence of learning supervision and work motivation on work commitment. The comprised population for this research was all civil servant teachers at junior high schools in Padang City, totaling 1247 people. The research sample consisted of 157 teachers using the cluster random sampling technique. The research used assessment scales and Likert scale model questionnaires as instruments. In addition, the data was analyzed using analytical techniques. The results indicate that the amount of work a teacher has can influence their level of work commitment. The level of achievement in supervision can increase teacher work commitment, and improving learning supervision and enhancing work motivation can increase work commitment.